2012
DOI: 10.3109/03014460.2012.689326
|View full text |Cite
|
Sign up to set email alerts
|

Development of multilocus putatively neutral DNA markers in the X-chromosome for population genetic studies in humans

Abstract: All eight DNA fragments seem to bear the characteristics to be considered as 'putatively neutral genetic markers' and thus, could be utilized for inference of human population and demographic histories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Population data from multiple individuals further enables in determination of the frequency of three different alleles ( FY*A , FY*B and FY*O ) which could be utilized in evolutionary inference of the FY gene [5], [6]. Since eco-climatic factors are highly variable in India (large longitudinal and latitudinal transects) with complex malaria epidemiology due to both P. vivax and P. falciparum infections [11] and Indians are genetically heterogeneous with complex population history [12], [13], [14]; we were interested to determine (i) the variable distribution of FY gene polymorphisms and genetic differentiations among populations living in different eco-climatic conditions, and (ii) possible correlation between FY gene polymorphisms and vivax malaria epidemiology by population genetic analyses in India. Although previous studies have indicated the distribution of different serological phenotypes of the Fy antigen in different local populations in India [15], [16], [17], [18], neither any survey on the distribution of different FY alleles representing the whole of India has been conducted, nor any correlation of FY polymorphisms to eco-climatic and/or vivax malaria epidemiology has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Population data from multiple individuals further enables in determination of the frequency of three different alleles ( FY*A , FY*B and FY*O ) which could be utilized in evolutionary inference of the FY gene [5], [6]. Since eco-climatic factors are highly variable in India (large longitudinal and latitudinal transects) with complex malaria epidemiology due to both P. vivax and P. falciparum infections [11] and Indians are genetically heterogeneous with complex population history [12], [13], [14]; we were interested to determine (i) the variable distribution of FY gene polymorphisms and genetic differentiations among populations living in different eco-climatic conditions, and (ii) possible correlation between FY gene polymorphisms and vivax malaria epidemiology by population genetic analyses in India. Although previous studies have indicated the distribution of different serological phenotypes of the Fy antigen in different local populations in India [15], [16], [17], [18], neither any survey on the distribution of different FY alleles representing the whole of India has been conducted, nor any correlation of FY polymorphisms to eco-climatic and/or vivax malaria epidemiology has been established.…”
Section: Introductionmentioning
confidence: 99%
“…; Bachtrog & Andolfatto ; Khan et al . ). This is because loci present in the X chromosome form accessible haplotypes in males and have small effective population size leading to lower recombination rate, lower mutation rate and faster genetic drift, resulting in greater Linkage Disequilibrium (LD) and population structure, as compared with autosomal DNA (Schaffner ; Tomas et al .…”
Section: Introductionmentioning
confidence: 97%
“…) and more recently in humans (Khan et al . ) and the malaria parasite (Gupta et al . ) in successfully inferring population genetic structure and demography of the respective species populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations